A "Trans-Dyadic" Perspective on the Goldwater Rule. Issue 6 (November 2017) - PLAKUN, ERIC M.
Abstract : The Goldwater Rule has been debated, redefined, and debated further since the election of Donald Trump as President of the United States. This column offers a perspective on the Goldwater Rule that moves beyond psychiatry's current preoccupation with precision DSM-5 diagnosis of individuals, which ethically requires consent or other legal authorization for release of diagnostic information to others, and into the realm of leadership as seen through the "trans-dyadic" lens of psychoanalytic understanding of large group processes on a societal level. Concepts from large group psychology are introduced to illustrate "trans-dyadic" perspectives on leadership that do not challenge the Goldwater Rule.